Respuesta agronómica de genótipos de Quinua (Chenopodium quinoa Willd) bajo conducciones controladas de estrés salino, en el campus universitario "La María" - Zambrano Noriega, Nelly Yuliana (2019)
The research was carried out in the Campus "La María", belonging to the State Technical University of Quevedo, for which thirty quinoa genotypes (Chenopodium quinoa Willd) were used under controlled conditions of saline stress. The objectives of the work were to: determine the effect of salinity on germination, the relative content of water in the leaves, root and biomass development, assessed at 8 and 15 dds, at 25 and 55 dds, at 35 and 60 days after planting Respectively. A completely randomized design (DCA) was applied with factorial arrangement, consisting of two factors: A. Genotypes (G1-G30) and B. salinity dose (D1: 0 mM NaCl and D2: 300 mM NaCl), with three repetitions. The results of the variables showed a highly significant difference (p-0.05) between the treatments; the application of NaCl in irrigation water did not affect the emergence of plants, recording the highest overall average (83%) compared to the control group (64%). However, it negatively and significantly affected the growth of plants, as well as the percentage of relative water content as NaCl accumulated in the soil increased the concentration of salts in the soil. The root system was also affected by the NaCl, causing an elongation of the main root, but, the root volume was considerably reduced, generating a lower production of biomass in plants under saline stress. It is concluded that daily irrigation with a concentration of 300 mM NaCl impairs the development of plants, however, genotypes O-1, O-2, O-3, O-5, O-10, X3, X4 and X5 were the least affected by the salts achieving the highest results. Key words: Quinoa, Sodium Chloride, Tolerance, Electrical Conductivity, Optional Halophilic Plants.